MENINGKATKAN KREATIVITAS SENI RUPA ANAK USIA 5 – 6 TAHUN MELALUI KEGIATAN FINGER PAINTING DI PAUD TERATAI DESA GELAM JAYA KABUPATEN TANGERANG - Diah Mardiana; Yogi Gumilar (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
This study aims to describe the implementation of fingerpainting activities and their benefits on the fine arts creativity of children aged 5-6 years at PAUD Teratai, Tangerang Regency. The study used a qualitative approach with a case study type. The research subjects consisted of 10 children from group B and a class teacher. Data collection techniques were carried out through observation, interviews, and documentation. Data were analyzed using the Miles and Huberman model through data reduction, data presentation, and drawing conclusions. The results showed that finger painting activities were able to increase children's creativity, especially in the ability to recognize colors, mix colors, self-confidence, independence, and produce unique works. This activity also provides opportunities for children to explore and express their imagination freely. Thus, finger painting is effectively used as a medium for learning fine arts in early childhood.